The Judicial Interpretation of Intimate Partner Homicide in China: An Empirical Analysis of Sentencing Practice Between 2016 and 2021 - Han, Xiao (Violence against women, 2025)
In recent years, China has endeavored to implement individualized sentencing for cases of intimate partner homicide (IPH), using both legal and extralegal factors, to protect potential female victims and female defendants. This study examines the factors influencing the sentencing of IPH, utilizing a sample comprising 921 cases from 2016 to 2021 on the China Judgments Online website. The results show that: (1) the legal factor “victim's fault” is the main reason for the leniency of sentencing for female defendants compared to male defendants; and (2) intimate partner relationships between defendants and victims can have a protective effect on sentencing.